2006
DOI: 10.1210/me.2006-0293
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Signaling System Is Present in the Postnatal Pituitary: Marked Expression and Regulatory Activity in the Newly Discovered Side Population

Abstract: Recently, we discovered in the adult anterior pituitary a subset of cells with side population (SP) phenotype, enriched for expression of stem/progenitor cell-associated factors like Sca1, and of Notch1 and Hes (hairy and enhancer of split) 1, components of the classically developmental Notch pathway. In the present study, we elaborated the expression of the Notch signaling system in the postnatal pituitary, and examined its functional significance within the SP compartment. Using RT-PCR, we detected in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 80 publications
4
77
0
Order By: Relevance
“…Activation of FGF and EGF can lead to increased pituitary stem cell numbers, as has been demonstrated in AP cell aggregate cultures (Chen et al 2006).…”
Section: Pituitary Regeneration and Impact Of Agingmentioning
confidence: 71%
See 3 more Smart Citations
“…Activation of FGF and EGF can lead to increased pituitary stem cell numbers, as has been demonstrated in AP cell aggregate cultures (Chen et al 2006).…”
Section: Pituitary Regeneration and Impact Of Agingmentioning
confidence: 71%
“…In general, there is no co-localization of PROP1 or SOX2 with hormones (Chen et al 2009;Fauquier et al 2008;Fu et al 2012a,b;Garcia-Lavandeira et al 2009;Gremeaux et al 2012;Yoshida et al 2009), supporting the general notion that stem cell conservators must be downregulated before differentiation starts. The NOTCH pathway is another essential regulator of pituitary embryogenesis (Kita et al 2007;Monahan et al 2009;Raetzman et al 2004;Zhu et al 2005Zhu et al , 2007, of which several components are upregulated in the adult (mouse) pituitary stem cell fraction (Chen et al 2006(Chen et al , 2009Vankelecom 2010) and are found expressed in some of the MZ and parenchymal S100 ĂŸ cells of the (rat) AP (Tando et al 2013). Some other transcriptional regulators that play an important role in pituitary embryonic development (such as Hesx1, the earliest known gene expressed in the pituitary primordium, Lhx4, Pax6, Otx2, Ascl1 and the Six/Eya/ Dach genes; Kelberman et al 2009;Zhu et al 2005Zhu et al , 2007 are also higher transcribed in the adult pituitary stem cell fraction (Chen et al 2006(Chen et al , 2009reviewed in Vankelecom 2010reviewed in Vankelecom , 2012, as well as the cyclin-dependent kinase inhibitor p57 that, during embryogenesis, emerges in the RP progenitor cells that stop cycling to embark on differentiation (Bilodeau et al, 2009;Vankelecom 2010;Vankelecom and Chen 2014).…”
Section: Pituitary Stem Cells: Expanding Molecular Portrayalmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a typical property of many cell types that possess properties of stem or progenitor cells. This side population has since been described for pituitaries of other vertebrates (Chen et al 2005(Chen et al , 2006van Rijn et al 2012). In time, additional markers of cells with this in vitro self-renewal capacity have been put forward to refine the characterisation of PSCs, including Nestin, PROP1, SOX9, GFRα2 and PRX1/2 (Gleiberman et al 2008;Yoshida et al 2009;Rizzoti et al 2013;GarciaLavandeira et al 2009;Higuchi et al 2014).…”
Section: Introductionmentioning
confidence: 99%